A general synthetic route to [Cu(X)(NHC)] (NHC = N-heterocyclic carbene, X = Cl, Br, I) complexes - Santoro, Orlando (Royal Society of Chemistry, 2013)

(untitled)
A one-pot procedure for the synthesis of [Cu(X)(NHC)] (X = Cl, Br, I) is reported. The reaction is applicable to a wide range of saturated and unsaturated NHC ligands, is scalable and proceeds under mild conditions using technical grade solvents in air.